Ojcowie Kościoła i manichejczycy wobec apokryfów na tle kryzysu pryscyliańskiego - Sordyl, Krzysztof (Vox Patrum, 2013)
In the Church of the first centuries some Fathers of the Church used the Apocrypha. But, the general tendency, which we can notice in the fourth century theology, is resignation from using them. It was connected, among other things, with creating the biblical canon. In Priscillian’s opinion, it is allowed to use the Apocrypha. The bishop of Avila propagating the right to use them contributed to spreading them, especially in Spain and Mediterranean Gaul. Priscillian was favourable to these texts, but careful, and so were some of the Fathers of the Church. In spite of it, it was reading the Apocrypha that contributed to accusing him of Manichaeism and Gnosticism. Mani and his followers also took advantage of the Apocrypha using novel extracts in which a fight for purity dominates and characters’ indomitability is shown. The anti-Priscillian literature unanimously condemned reading the Apocrypha by Priscillianists. The synod in Toledo does it as well as the first synod in Braga, the popes Innocent I and Leon the Great and the writers Augustinian, Orosius, Turibius. The Priscillianists refering to the Apocrypha created sabellian conception of the Holy Trinity. Various texts presumably edited by the Priscillianists (Monarchiani Prologues, The Revelation of St. Thomas, Pseudo-Titus Letter) contain references to the Apocrypha. It should be noticed that the Priscillianist exegetic principle was to explain canon books by means of other texts. Besides, D. de Bruyne presents the Apocrypha ascribed to the Priscillianists; this collection comprises the following texts: Collectio de diversis sententiis, Apocalypsis, Sermo S. Augustini Episcopi, Homilia de die iudicii, De parabolis Salomonis, Liber ,,canon in Ebreica” Hieronymi presbyteri. He also made an attempt to establish a probable list of the Apocrypha which the Priscillian community might have used.